European forest policy and governance : an integrative analytical framework - Aggestam, Filip (New York, NY : Routledge, 2025)
"This book provides a state-of-the-art overview covering distinct and relevant aspects of forest policy processes in Europe, presenting a fresh perspective on different analytical approaches, theories, and frameworks. Set against the background of a changing world, driven by significant social, environmental and economic developments, in Europe and elsewhere, there is a growing need for an improved understanding of forest governance and how to analyse the forest policymaking processes. This book introduces the reader to some of the key issues typically encountered in reviewing proposed as well as established forest policies, focusing on five socially relevant topics for the forest-based sector today, namely: European forest governance under a green new deal Systemic changes and the circular (bio-)economy Social changes connected with forest ownership and forest actors Nature conservation and the pursuit of multifunctional forests Living with forest fires and climate change In so doing, this book presents a set of timely and rich case studies relevant to the study of forest governance. In the final chapter, it puts forward an innovative and systematic method for selecting the most appropriate analytical tool that accounts for the constraints and objectives involved in monitoring forest policy. The book is accompanied by chapter-level exercises and an online annex which details the various approaches, theories and frameworks discussed in the book, providing direct links back to individual chapters, discussion points and a step-by step guide for how each method can be applied. This book will be of essential reading for forestry students and scholars, and professionals and policymakers working on forest policy and forest management"--
1. Introduction -- 2. Forest governance: the EU perspective -- 3. Overview of theories and approaches used in forest policy research -- 4. Policy pathways for the European Green Deal and the EU Forest Strategy -- 5. Systemic change for the forest-based sector: implementing the circular bioeconomy -- 6. Forest ownership and the provision of forest ecosystem services -- 7. Forest fires, resilience, and climate change -- 8. Nature protection, productivity, and multifunctional forest use -- 9. A framework for integrative forest policy analysis -- 10. Conclusions
Keywords: Forest policy -- Europe; Forest management -- Europe; Forests and forestry -- Europe; BUSINESS & ECONOMICS / Environmental Economics; NATURE / Ecology